Analytical Study of the Impact of Earthquakes on the AL BALLOUTA Dam Using Numerical Modeling - صالح, علا; منذر حماد , (Latakia University Journal -Engineering Sciences Series, 2023)
This study uses numerical modeling to analyze the effects of earthquakes and demonstrates how to use the Finite Element Method (FEM) to determine the static and dynamic stability of embankments dams. The AL Ballouta dam was chosen as a case study to monitor the most significant changes that occur to it after the earthquake for this reason, and as a result, we developed a suitable numerical model for the studied issue using the Geo-Studio software package. This software package contains within it sub-programs used in the research, such as the Slope/w program, which simulates the problem in static case, and the Quake/w program, which simulates the problem in dynamic case in order to calculate the safety parameters in the most dangerous state of the load (maximum load state). The study also proved that the dam is stable in all cases of loading and that the finite element method is better than other traditional methods because it allows testing deformation and stress scenarios that the dam may be offers to, and provides the possibility of a design that achieves the safety required to face all of these scenarios.